Narration in the early stories by Kuzma Chorny - Chasnok, Iryna Ch. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to analysis of the narrative organization of early works by Kuzma Chorny. Reviewed short stories («On the border (Pictures from the borderline life)», «On Guard», «My duty is small», «We will live», «Iron cry», «Feelings», «Pines say») have clearly two main narrative dominants in Kuzma Chornyi’s prose as the orientation on mental eventfullness and the agitation narrative strategy. On this view, the techniques like journalism, metanarrative (aspiration of characters or narrator to the collective community), uninformative dialogues, creating intrigue through unknown lines and unnamed characters, giving a narrative to descriptions, the orientation on the inner, mental changes in the nature of the character are in frequent use by Kuzma Chorny in these works. Kuzma Chorny included the above narrative techniques in future works (novels «The Sister», «The Earth», «Search for the Future», «The Milky Way», novella «Liuba Luk’ianskaia», etc.).